2008
DOI: 10.1007/s00285-008-0242-7
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical analysis of physiological and morphological aspects of wound closure

Abstract: A computational algorithm to study the evolution of complex wound morphologies is developed based on a model of wound closure by cell mitosis and migration due to Adam [Math Comput Model 30(5-6):23-32, 1999]. A detailed analysis of the model provides estimated values for the incubation and healing times. Furthermore, a set of inequalities are defined which demarcate conditions of complete, partial and non-healing. Numerical results show a significant delay in the healing progress whenever diffusion of the epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…Simulations are in agreement with available lung tissue data of human patients [163]. Javierre et al [164] analyzed the roles of diffusion, closure rate, and wound geometry on healing kinetics and concluded that healing is always initiated at regions with high curvatures.…”
Section: Models With Internal Structuresupporting
confidence: 66%
“…Simulations are in agreement with available lung tissue data of human patients [163]. Javierre et al [164] analyzed the roles of diffusion, closure rate, and wound geometry on healing kinetics and concluded that healing is always initiated at regions with high curvatures.…”
Section: Models With Internal Structuresupporting
confidence: 66%
“…The first model describes a traveling wave analysis, whereas the second paper assesses fundamental mathematical questions on existence, uniqueness of solutions, and the mathematical nature of the moving boundary separating the wound from the undamaged tissue. Javierre et al (2009) presents a numerical solution method for the moving boundary problem.…”
Section: Introductionmentioning
confidence: 99%
“…A key contribution is the work of Fung & Liu (1989), amongst many others, which demonstrates that the volumetric growth of blood vessels induces a change in the natural configuration of the tissue, and induces residual stresses. Diffusion and cells migration models (Javierre et al, 2009;Cumming et al, 2010;Boyle et al, 2011) are other interesting approaches to the problem of biological tissue adaptation.…”
Section: Motivationmentioning
confidence: 99%